1999
DOI: 10.1046/j.1525-1470.1999.00022.x
|View full text |Cite
|
Sign up to set email alerts
|

Dermatologic Findings in Anorexia and Bulimia Nervosa of Childhood and Adolescence

Abstract: The cutaneous signs of anorexia nervosa (AN) and bulimia nervosa (BN) have been described previously in adult patients. For the first time, we present here dermatologic findings in children and adolescents suffering from eating disorders. Thirty consecutive young anorexic and bulimic inpatients (8 to 17 years of age, mean 15.1 years) underwent a standardized dermatologic examination. Patients were checked for abnormalities of the skin including atopic stigmata, dermographism, hair, nails, and oral cavity. Seru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
0
4

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(53 citation statements)
references
References 16 publications
5
44
0
4
Order By: Relevance
“…This finding appears consistent with Harbauer [46]who describes nail-biting as a form of auto-aggressiveness that in some cases develops into an eating disorder later. This result also agrees with Schulze et al [47], who found onychophagia in 27% and scars in 12% of eating-disordered patients. Although nail-biting is described as an antecedent or comorbid factor of eating disorders [48], it does not appear to be specific for anorexia or bulimia nervosa, since our patients with PSD reported similarly high rates.…”
Section: Discussionsupporting
confidence: 93%
“…This finding appears consistent with Harbauer [46]who describes nail-biting as a form of auto-aggressiveness that in some cases develops into an eating disorder later. This result also agrees with Schulze et al [47], who found onychophagia in 27% and scars in 12% of eating-disordered patients. Although nail-biting is described as an antecedent or comorbid factor of eating disorders [48], it does not appear to be specific for anorexia or bulimia nervosa, since our patients with PSD reported similarly high rates.…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with the literature, xerosis, hair effluvium, acne, cheilitis, gingivitis, nail changes and acrocyanosis were the most frequently observed symptoms [2, 3, 5, 6, 7]. The pathogenetic mechanism responsible for the development of cutaneous signs in AN has been debated in many studies [9, 10, 11, 12, 13, 14, 15, 16].…”
Section: Discussionsupporting
confidence: 59%
“…Eating disorders are becoming an epidemic also in Europe, particularly among young women, but European studies concerning this topic are few [1, 2, 3]. Eating disorders mainly include anorexia nervosa (AN), bulimia nervosa (BN) and eating disorders not specified.…”
Section: Introductionmentioning
confidence: 99%
“…Die Hautveränderungen der Akne befinden sich v. a. fazial und am Rücken, verbunden mit Kratzexkoriationen [4]. Zur Akne kann es zum einen durch das Fasten und Hungern bei AN kommen, zum anderen sind Patienten mit AN meist jugendliche Mädchen -der Häufigkeitsgipfel liegt zwischen dem 14. und 16.…”
Section: Akneunclassified